Gingival Biotype Classification, Assessment, and Clinical Importance: A Review - Shah, Harish Kumar; Sharma, Shivalal; Shrestha, Sajeev (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
A normal scalloped gingival line at the cement enamel junction of the teeth forms one of the components of an aesthetic smile. Clinicians handle gingiva in several periodontal procedures and the resulting gingival architecture is not always ideal. In the era of aesthetic-driven dental therapy, it is important that a clinician should be well aware of all the prognostic factors that may affect the final aesthetic outcome of dental treatment. Gingival biotype is one of the important factors which influences indications and outcome of various periodontal, restoratives, surgical, and implant therapy. Thin gingival biotype responds differently than thick gingival biotype. Gingival biotype assessment before various dental-related procedures is mandatory now to achieve a predictable and stable gingival margin position. This review describes the various classifications, methods of assessment, and clinical importance of gingival biotype during dental treatment.